Legal culture of judges and employees of the judicial system in the Republic of Kazakhstan: Theory and Practice (Journal of actual problems of jurisprudence, 2018)
The aim of the articles is to study theoretical and practical aspects in improving legal culture of judges in the Republic of Kazakhstan. Particular attention is given to the aspects of the legal mentality and establishment of the professional legal awareness of judges. In this article influence of globalization on development of legal culture of Kazakhstan society opens up also. Methods of research: historical, comparative-law, structural-functional, logical, technical.Key words: legal culture, legal awareness, mentality, legal nihilism.